Assessment of phosphorus availability in soil by introducing P-solubilizing novel bacterial and fungal strains of Lower Himalaya. Issue 13 (20th July 2019) - Hafeez, Farhan; Amin, Bilal Ahmad Zafar; Akbar, Uzair; Iqbal, Akhtar; Faridullah,; Bilal, Muhammad; Nazir, Rashid
ABSTRACT: Phosphorus ( P ) is an essential element for soil quality and plant growth. But little is known about P fractions consequent to microbial inoculation in soils amended with inorganic phosphorus. In this regard, the overall soil P fractions after microbial treatments varied as hydrochloric acid – P (HCl- P ) > Sodium hydroxide – P (NaOH- P ) > Sodium bicarbonate – P (NaHCO3 - P ) > Water – P (H2 O- P ) determined through sequential fractionation. Inorganic P amendment of soil increased residual P fractions indicating non-availability of chemical P fertilizers added in soil. Bacterial–fungal co-inoculation, significantly increased NaHCO3 - P and H2 O- P fractions, as compared to mono inoculations and un-inoculated controls. Inoculated microbial populations increased in numbers contributing to the modification of the soil pH. In soil without TriCalcium Phosphate (TCP), microbial treatments showed a reduced pH compared to the control, with a maximum pH decrease in mono bacterial inoculations. In conclusion, tested bacterial and fungal strains exhibited efficient P solubilization in soil, and thus, have potential to be used as biofertilizers, subject to other necessary trials.